PRODUCTIVE PERFORMANCE OF MAIZE CROP IRRIGATED WITH AND WITHOUT WATER DEFICIT IN DIFFERENT PLANT ARRANGEMENTS - CARVALHO, MARCUS WILLAM LOPES; BASTOS, EDSON ALVES; CARDOSO, MILTON JOSÉ; ANDRADE JÚNIOR, ADERSON SOARES DE; SILVA, MARCELO RIBEIRO (REVISTA BRASILEIRA DE MILHO E SORGO, 2020)
The objective of the present study was to evaluate the effects of row spacing and planting density, under different water regimes, on dry grain production of the maize hybrid AG -1051, in Teresina, Piauí. Two experiments were conducted with the use of a conventional sprinkler system for irrigation, being one with 100% and the other with 50% crop evapotranspiration (ETc) replacement. A randomized block experimental design was used, in a 5x2 factorial scheme, combining five planting densities (PD) (20,000; 40,000; 60,000; 80,000; and 100,000 plants ha-1) and two spacings between rows (RS) (0.5 and 1.0 m), with four replications. The weight of 100 grains, cob percentage, grain yield, and water use efficiency were evaluated. The increment of planting density caused a linear decrease in the 100-grain weight and increment of the cob percentage in relation to the total ear weight. Under full irrigation regime, the combination of the 0.5 m row spacing and planting density of 72,000 plants ha-1 provided maximum yield of 7.2 Mg ha-1. Under water deficit condition, the maximum yield of 4.8 Mg ha-1 was reached in the combination of the 0.5 m row spacing and planting density of 67,000 plants ha-1..The total water depth of 419 mm provided maximum WUE of 1.70 kg m-3. The total water depth of 268 mm caused a reduction in WUE with maximum point of 1.54 kg m-3.